Improving teacher education practices through self-study - Loughran, J. John; Russell, Tom, 1941- (RoutledgeFalmer, 2002)
Self-study in teacher education is a growing field and a natural progression from the concept of reflective practice for pre-service teachers. This book is designed to introduce teacher educators to the theory and practice of self-study, in order to explore, understand and improve their teaching about teaching. With studies from an international range of contributors, this book illustrates a variety of approaches to self-study. It describes the issues that teacher educators have chosen to study, how they carried out their research and what the learning outcomes were. Throughout, the emphasi.